2009
DOI: 10.1364/ol.34.002873
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-assisted single-photon spectrograph

Abstract: We demonstrate the implementation of a fiber-integrated spectrograph utilizing chromatic group velocity dispersion (GVD) in a single-mode fiber. By means of GVD we stretch an ultrafast pulse in time in order to spectrally resolve single photons in the time domain, detected by single-photon counting modules with very accurate temporal resolution. As a result, the spectrum of a very weak pulse is recovered from a precise time measurement with high signal-to-noise ratio. We demonstrate the potential of our techni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
148
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 19 publications
1
148
0
Order By: Relevance
“…If the two entangled squeezed modes are generated in a factorizable state, we should see that the joint spectral probability distribution is also factorizable [8,9]. In the lowsqueezing limit, where a single photon pair is generated, it was recently shown that it is possible to generate pairs with an effective mode number that is close to the ideal value of 1 [8][9][10][11][12][13][14][15]. Hong-Ou-Mandel interference provides a measure of the similarity of the spectral distributions of the signal and idler modes.…”
Section: Introductionmentioning
confidence: 98%
“…If the two entangled squeezed modes are generated in a factorizable state, we should see that the joint spectral probability distribution is also factorizable [8,9]. In the lowsqueezing limit, where a single photon pair is generated, it was recently shown that it is possible to generate pairs with an effective mode number that is close to the ideal value of 1 [8][9][10][11][12][13][14][15]. Hong-Ou-Mandel interference provides a measure of the similarity of the spectral distributions of the signal and idler modes.…”
Section: Introductionmentioning
confidence: 98%
“…The bandwidth is adjusted to ensure a decorrelated PDC state. We characterize the spectral properties of the PDC photons by measuring their joint spectral intensity with a time-of-flight spectrometer 31 , consisting of a pair of dispersive fibres and a lowjitter superconducting nanowire single-photon detector (SNSPD; Photon Spot). From this measurement, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…in conjunction with a superconducting nanowire single photon detector (Opus One, Quantum Opus) and a time-tagging module (TTM8000, Austrian Institute of Technology) in order to build a calibrated spectrometer [39]. This system stretches the unfiltered signal 2/idler 2 pulses in time, according to their spectral components [40][41][42].…”
Section: Resultsmentioning
confidence: 99%